(untitled) (Journal of Patan Academy of Health Sciences, 2017)
Introductions: Gestational age is estimated on the basis of last normal menstrual period and the measurement of foetal growth parameters by ultrasonography. The lack of accurate recollection of the last menstrual period and dependence of growth parameters on intra-uterine environment, physical and mental well-being of the mother, maternal nutrition and genetic factors leads to the over or under estimation of gestational age. The aim of this study was to investigate the correlation between placental thicknesses (PT) in normal singleton Nepalese foetuses. Methods: This was a cross sectional study of ultrasound measurement of placental thickness during 2nd and 3rd trimester pregnancy from April 2015 to October 2015 at Department of Radiology, Suraksha Hospital, Biratnagar, Nepal. All viable singleton uncomplicated pregnancies, history of regular menstruation with known LNMP were included. Microsoft Excel and SPSS 17 were used for data analysis. Pearson’s correlation analysis was used for correlation between placental thickness and gestational age. Statistical tests were two-tailed with p<0.01 as statistical significance. Results: There were 592 pregnant women who met the criteria. Placental thickness increased by 0.86 mm in every week of increase in gestational age. The maximum mean PT of 40.42±1.05 mm was observed at 39th week. There was a significant positive correlation between placental thickness and gestational age, correlation coefficient r=0.986 (P<0.001). Conclusions: PT was found to be a reliable alternative predictor in calculating gestational age. Measurement of PT should be done routinely during obstetrics ultrasonography.